Divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material and preparation method and application thereof
By doping binary manganese ions in CS3CD2CL7 and preparing cadmium cadmium, halide nanocrystalline flashing body materials, the problem of stability and efficiency of traditional flash body materials in X -ray imaging has been solved. Rate imaging.
Patent Information
- Application Number
- CN202411939702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional scintillator materials have problems such as long synthesis cycle, high production cost, low luminescence efficiency, low spatial resolution and poor stability in X-ray imaging, which cannot meet the higher X-ray imaging needs.
By doping divalent manganese ions into Cs3Cd2Cl7, a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material was prepared to convert cyan light into yellow light and achieve efficient yellow light emission, and used thermal injection method to prepare scintillator films to improve their optical properties.
Achieving a high -efficiency yellow light launch with a quantum efficiency of 20.6%, the fluorescent life is 0.652 μs, the flashing strength of the flashing film is about 1.3067 times of CSI: TL wafer, the imaging resolution reaches 16 LP/mm, suitable for X -ray medicine Imaging, non -destructive detection and industrial exploring areas.
Smart Images

Figure CN119349644A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scintillator materials, and in particular to a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material and a preparation method and application thereof. Background Art
[0002] X-ray detectors are widely used in medical radiological diagnosis, industrial non-destructive testing, and core components of high-value instruments. Traditional scintillators (such as NaI: Tl and CsI: Tl are the most common commercial scintillators) have been widely used in non-destructive testing, medical imaging, space detectors, etc. They show relatively high light yield and a decay time of about 200ns. However, traditional scintillators have problems such as long synthesis cycle, high production cost, low luminous efficiency, low spatial resolution, and poor stability due to their strong hygroscopicity. These have hindered their further development in X-ray imaging and cannot meet the higher requirements of X-ray imaging.
[0003] In recent years, metal halide scintillator materials, especially lead-based halide perovskites, have attracted great attention due to their high X-ray absorption and excellent optical properties, and have become a research hotspot in the field of X-ray detection. The efficient luminescence performance and defect tolerance of these materials give them great application potential in X-ray imaging technology, but there are still problems such as unsatisfactory radiation stability and inevitable self-absorption, which greatly reduces the light output efficiency. In addition, lead is a toxic element, which limits their commercialization and large-scale application. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to solve the defects in the existing technology, the development of stable, high light yield, non-lead metal halide scintillator materials with large Stokes shift has been favored by researchers. Metal halide materials with excellent luminescence and optoelectronic properties generally exist in the form of nanocrystals, single crystals and polycrystalline powders. Among them, all-inorganic metal halide nanocrystalline materials are particularly noteworthy. This type of material not only has high photoluminescence efficiency, tunable luminescence wavelength, high color purity, strong light absorption, low exciton binding energy and high carrier mobility, but also has higher light / thermal stability and humidity stability compared to many organic-inorganic hybrid metal halides.
[0006] Another object of the present invention is to provide a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which is formed by doping divalent manganese ions into Cs3Cd2Cl7 to achieve the conversion of cyan light into yellow light, thereby achieving efficient yellow light emission with a quantum efficiency of 20.6% and a fluorescence lifetime of 0.652μs.
[0007] Another object of the present invention is to provide a method for preparing divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which has the advantages of simple process, low cost, green and pollution-free, and can realize large-scale industrial production.
[0008] Another object of the present invention is to provide a scintillator film and a preparation method thereof, wherein the scintillator film is prepared by dispersing a cadmium-based metal halide nanocrystalline scintillator material doped with divalent manganese ions in a polymer precursor and using a doctor blade coating method, and the scintillation intensity is 1.3067 times that of a commercial scintillator CsI: Tl wafer, and the minimum detection limit is 4.0138 μGy air / s, and the imaging resolution is about 16 lp / mm, which can be effectively applied to X-ray medical imaging, non-destructive testing, industrial flaw detection and other fields.
[0009] In order to achieve these purposes and other advantages according to the present invention, a divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material is provided, the chemical formula of which is: A3B 2(1-a) Mn 2a X7, wherein A is Cs, B is Cd, X is Cl, and 0<a≤20.
[0010] Preferably, 0<a≤0.2.
[0011] Preferably, a is 0.1.
[0012] The present invention also provides a method for preparing a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which comprises the following steps:
[0013] Step 1: Weigh each raw material according to the general chemical formula to prepare a precursor solution;
[0014] Step 2, heating the precursor solution under vacuum;
[0015] Step 3: The vacuum environment is switched to an inert gas atmosphere, and a hot injection process is used to prepare a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material.
[0016] Preferably, step three specifically includes: switching the vacuum environment to a nitrogen atmosphere, raising the temperature to 240° C. at a rate of 5° C. / min, rapidly injecting 800 μL of trimethylchlorosilane with a syringe, and controlling the reaction time within 10 to 12 seconds.
[0017] Preferably, step one specifically comprises: weighing cadmium carbonate, cesium acetate and manganese carbonate according to the general chemical formula, placing them in a 50 mL three-necked round-bottom flask, adding octadecene, oleic acid, oleylamine and acetic acid in sequence, placing the flask on a constant temperature magnetic stirrer, evacuating the flask and heating it to 60° C., and stirring continuously for 30 minutes to obtain a precursor solution.
[0018] The present invention also provides a scintillator film, which comprises the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material.
[0019] The present invention also provides a method for preparing a scintillator film, which comprises: dispersing the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material in a polymer precursor, and preparing the scintillator film by a scraping method.
[0020] Preferably, the polymer is polystyrene, polyvinylidene fluoride or polymethyl methacrylate.
[0021] Another object of the present invention is to achieve the above object through the application of the scintillator film in X-ray medical imaging, non-destructive testing and industrial flaw detection.
[0022] The present invention has at least the following beneficial effects:
[0023] First, the divalent manganese ion-doped cadmium-based metal halide nanocrystal scintillator material of the present invention is prepared by doping divalent manganese ions in Cs3Cd2Cl7, realizing the conversion of cyan light to yellow light, and further realizing efficient yellow light emission with a quantum efficiency of 20.6% and a fluorescence lifetime of 0.652μs. Compared with the prior art, it can effectively expand the types of scintillator nanocrystals, and has good stability and excellent X-ray scintillation performance (the prepared scintillator film has a high resolution).
[0024] Second, the preparation method of the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material of the present invention is low-cost, green and pollution-free, has a short synthesis cycle, and can realize large-scale industrial production.
[0025] Third, the scintillator film made of the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material of the present invention has a scintillation intensity of about 1.3067 times that of the CsI: Tl wafer, and the minimum detection limit is 4.0138 μGy air / s, and the imaging resolution is about 16 lp / mm, which can be effectively applied to X-ray medical imaging, non-destructive testing, industrial flaw detection and other fields.
[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 Cs3Cd obtained in Example 2 of the present invention 1.8 Mn 0.2 Crystal structure of Cl7 nanocrystals;
[0029] Figure 2 XRD patterns (A) and 20-25° diffraction peak magnification (B) of the nanocrystals prepared in Examples 1 to 4 of the present invention and Comparative Example 1;
[0030] Figure 3 Cs3Cd obtained in Example 2 of the present invention 1.8 Mn 0.2 Thermogravimetric analysis of Cl7 nanocrystals;
[0031] Figure 4 The photoluminescence excitation spectrum (A) and the photoluminescence emission spectrum (B) of the nanocrystals prepared in Examples 1 to 4 of the present invention and Comparative Example 1;
[0032] Figure 5 Cs3Cd obtained in Example 2 of the present invention 1.8 Mn 0.2 PL decay curve of Cl7 nanocrystals;
[0033] Figure 6 Cs3Cd obtained in Example 2 of the present invention 1.8 Mn 0.2 Quantum yield analysis diagram of Cl7 nanocrystals;
[0034] Figure 7 Cs3Cd obtained in Example 2 of the present invention 1.8 Mn 0.2 Transmission electron micrograph of Cl7 nanocrystals;
[0035] Figure 8Cs3Cd obtained in Example 5 of the present invention 1.8 Mn 0.2 Comparison of the radiant luminescence spectra of Cl7@PS scintillator film and commercial CsI: Tl scintillator wafer;
[0036] Fig. 9 Cs3Cd obtained in Example 5 of the present invention 1.8 Mn 0.2 Minimum detection limit diagram of Cl7@PS scintillator film;
[0037] Fig.10 Cs3Cd obtained in Example 5 of the present invention 1.8 Mn 0.2 Image of the spring inside the capsule under X-ray imaging of the Cl7@PS scintillator film;
[0038] Fig.11 Cs3Cd obtained in Example 5 of the present invention 1.8 Mn 0.2 Photo of the Cl7@PS scintillator film imaging the internal circuit of the chip;
[0039] Fig.12 Cs3Cd obtained in Example 5 of the present invention 1.8 Mn 0.2 Image of the Cl7@PS scintillator film on a standard X-ray resolution lead plate (A) and a partial magnified image (B). DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0041] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0042] In the present invention, cesium acetate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., cadmium carbonate and manganese carbonate were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; toluene was purchased from Sinopharm Group, n-hexane was purchased from Lianlong Bohua (Tianjin) Pharmaceutical Chemistry Co., Ltd., and polystyrene (PS) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0043] Example 1
[0044] A divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material, the chemical formula of which is Cs3Cd 1.9 Mn 0.1 Cl7, the preparation method thereof comprises the following steps:
[0045] Step 1: Place cadmium carbonate (0.2172 g), cesium acetate (0.2719 g) and manganese carbonate (0.0156 g) in a 50 mL three-necked round-bottom flask, add octadecene (34 mL), oleic acid (5.6 mL), oleylamine (1.23 mL) and acetic acid (400 μL) in sequence, place on a constant temperature magnetic stirrer, evacuate the flask and heat to 60 ° C, and continue stirring for 30 minutes to obtain a precursor solution;
[0046] Step 2: Continue heating the precursor solution obtained in step 1 to 105° C. under vacuum and stir for two hours;
[0047] Step 3: Switch the atmosphere in the three-necked round-bottom flask to a nitrogen atmosphere, and raise the temperature to 240°C at a rate of 5°C / min. During this process, the solution gradually turns into a transparent yellow color. After reaching 240°C, quickly inject 800 μL of trimethylsilyl chloride with a syringe, and control the reaction time within 10 to 12 seconds.
[0048] Step 4: quickly place the three-necked round-bottom flask into an ice-water bath to cool and obtain a suspension;
[0049] Step 5: Divide the suspension obtained in step 4 into two equal parts and transfer them into 50 mL centrifuge tubes respectively. Add methyl acetate (the volume ratio of methyl acetate to the suspension is 1:1) as an anti-solvent and centrifuge at 10,000 rpm for 7 min to obtain a white precipitate.
[0050] Step 6: remove the supernatant, add 10 mL of n-hexane as a dispersant to the white precipitate obtained in step 5, use an ultrasonic cleaner to redisperse the powder to form a suspension, and then add 20 mL of methyl acetate to repeat the washing;
[0051] Step 7: Put the washed powder into a vacuum drying oven and dry it for 12 hours to obtain a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which is composed of Cs3Cd 1.9 Mn 0.1 Cl7 nanocrystals were dispersed in n-hexane for further characterization.
[0052] Example 2
[0053] A divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material, the chemical formula of which is Cs3Cd 1.8 Mn 0.2 Cl7, the preparation method thereof comprises the following steps:
[0054] Step 1: Place cadmium carbonate (0.2058 g), cesium acetate (0.2719 g) and manganese carbonate (0.0311 g) in a 50 mL three-necked round-bottom flask, add octadecene (34 mL), oleic acid (5.6 mL), oleylamine (1.23 mL) and acetic acid (400 μL) in sequence, place on a constant temperature magnetic stirrer, evacuate the flask and heat to 60 ° C, and continue stirring for 30 minutes to obtain a precursor solution;
[0055] Step 2: Continue heating the precursor solution obtained in step 1 to 105° C. under vacuum and stir for two hours;
[0056] Step 3: Switch the atmosphere in the three-necked round-bottom flask to a nitrogen atmosphere, and raise the temperature to 240°C at a rate of 5°C / min. During this process, the solution gradually turns into a transparent yellow color. After reaching 240°C, quickly inject 800 μL of trimethylsilyl chloride with a syringe, and control the reaction time within 10 to 12 seconds.
[0057] Step 4: quickly place the three-necked round-bottom flask into an ice-water bath to cool and obtain a suspension;
[0058] Step 5: Divide the suspension obtained in step 4 into two equal parts and transfer them into 50 mL centrifuge tubes respectively. Add methyl acetate (the volume ratio of methyl acetate to the suspension is 1:1) as an anti-solvent and centrifuge at 10,000 rpm for 7 min to obtain a white precipitate.
[0059] Step 6: remove the supernatant, add 10 mL of n-hexane as a dispersant to the white precipitate obtained in step 5, use an ultrasonic cleaner to redisperse the powder to form a suspension, and then add 20 mL of methyl acetate to repeat the washing;
[0060] Step 7: Put the washed powder into a vacuum drying oven and dry it for 12 hours to obtain a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which is composed of Cs3Cd 1.8 Mn 0.2 Cl7 nanocrystals were dispersed in n-hexane for further characterization, Cs3Cd 1.8 Mn 0.2 The crystal structure of Cl7 nanocrystals is as follows Figure 1 shown.
[0061] Example 3
[0062] A divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material, the chemical formula of which is Cs3Cd 1.7 Mn 0.3 Cl7, the preparation method thereof comprises the following steps:
[0063] Step 1: Place cadmium carbonate (0.1944 g), cesium acetate (0.2719 g) and manganese carbonate (0.0467 g) in a 50 mL three-necked round-bottom flask, add octadecene (34 mL), oleic acid (5.6 mL), oleylamine (1.23 mL) and acetic acid (400 μL) in sequence, place on a constant temperature magnetic stirrer, evacuate the flask and heat to 60 ° C, and continue stirring for 30 minutes to obtain a precursor solution;
[0064] Step 2: Continue heating the precursor solution obtained in step 1 to 105° C. under vacuum and stir for two hours;
[0065] Step 3: Switch the atmosphere in the three-necked round-bottom flask to a nitrogen atmosphere, and raise the temperature to 240°C at a rate of 5°C / min. During this process, the solution gradually turns into a transparent yellow color. After reaching 240°C, quickly inject 800 μL of trimethylsilyl chloride with a syringe, and control the reaction time within 10 to 12 seconds.
[0066] Step 4: quickly place the three-necked round-bottom flask into an ice-water bath to cool and obtain a suspension;
[0067] Step 5: Divide the suspension obtained in step 4 into two equal parts and transfer them into 50 mL centrifuge tubes respectively. Add methyl acetate (the volume ratio of methyl acetate to the suspension is 1:1) as an anti-solvent and centrifuge at 10,000 rpm for 7 min to obtain a white precipitate.
[0068] Step 6: remove the supernatant, add 10 mL of n-hexane as a dispersant to the white precipitate obtained in step 5, use an ultrasonic cleaner to redisperse the powder to form a suspension, and then add 20 mL of methyl acetate to repeat the washing;
[0069] Step 7: Put the washed powder into a vacuum drying oven and dry it for 12 hours to obtain a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which is composed of Cs3Cd 1.7 Mn 0.3 Cl7 nanocrystals were dispersed in n-hexane for further characterization.
[0070] Example 4
[0071] A divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material, the chemical formula of which is Cs3Cd 1.6 Mn 0.4 Cl7, the preparation method thereof comprises the following steps:
[0072] Step 1: Place cadmium carbonate (0.1830 g), cesium acetate (0.2719 g) and manganese carbonate (0.0622 g) in a 50 mL three-necked round-bottom flask, add octadecene (34 mL), oleic acid (5.6 mL), oleylamine (1.23 mL) and acetic acid (400 μL) in sequence, place on a constant temperature magnetic stirrer, evacuate the flask and heat to 60 ° C, and continue stirring for 30 minutes to obtain a precursor solution;
[0073] Step 2: Continue heating the precursor solution obtained in step 1 to 105° C. under vacuum and stir for two hours;
[0074] Step 3: Switch the atmosphere in the three-necked round-bottom flask to a nitrogen atmosphere, and raise the temperature to 240°C at a rate of 5°C / min. During this process, the solution gradually turns into a transparent yellow color. After reaching 240°C, quickly inject 800 μL of trimethylsilyl chloride with a syringe, and control the reaction time within 10 to 12 seconds.
[0075] Step 4: quickly place the three-necked round-bottom flask into an ice-water bath to cool and obtain a suspension;
[0076] Step 5: Divide the suspension obtained in step 4 into two equal parts and transfer them into 50 mL centrifuge tubes respectively. Add methyl acetate (the volume ratio of methyl acetate to the suspension is 1:1) as an anti-solvent and centrifuge at 10,000 rpm for 7 min to obtain a white precipitate.
[0077] Step 6: remove the supernatant, add 10 mL of n-hexane as a dispersant to the white precipitate obtained in step 5, use an ultrasonic cleaner to redisperse the powder to form a suspension, and then add 20 mL of methyl acetate to repeat the washing;
[0078] Step 7: Put the washed powder into a vacuum drying oven and dry it for 12 hours to obtain a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material, which is composed of Cs3Cd 1.6 Mn 0.4 Cl7 nanocrystals were dispersed in n-hexane for further characterization.
[0079] Example 5
[0080] The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material Cs3Cd prepared in Example 2 1.8 Mn 0.2 Cl7 preparation of scintillator film: Cs3Cd 1.8 Mn 0.2 The Cl7@PS scintillator film specifically comprises the following steps:
[0081] Step 1: Cs3Cd prepared in Example 2 1.8 Mn0.2 The Cl7 divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material is placed in a mortar and ground carefully to obtain divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material powder;
[0082] Step 2, dissolving 2 g of polystyrene (PS) in 6 mL of toluene solvent to obtain a polymer solution;
[0083] Step 3: Mix the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material powder obtained in step 1 with the polymer solution obtained in step 2, stir evenly, then apply it onto a smooth substrate (the substrate can be a PVC board), and dry it naturally until the solvent evaporates to obtain Cs3Cd 1.8 Mn 0.2 Cl7@PS scintillator film.
[0084] Example 6
[0085] The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material Cs3Cd prepared in Example 2 1.8 Mn 0.2 Cl7 preparation of scintillator film: Cs3Cd 1.8 Mn 0.2 The Cl7@PMMA scintillator film specifically comprises the following steps:
[0086] Step 1: Cs3Cd prepared in Example 2 1.8 Mn 0.2 The Cl7 divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material is placed in a mortar and ground carefully to obtain divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material powder;
[0087] Step 2, dissolving 2 g of polymethyl methacrylate (PMMA) in 6 mL of toluene solvent to obtain a polymer solution;
[0088] Step 3: Mix the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material powder obtained in step 1 with the polymer solution obtained in step 2, stir evenly, then apply it onto a smooth substrate (the substrate can be a PVC board), and dry it naturally until the solvent evaporates to obtain Cs3Cd 1.8 Mn 0.2 Cl7@PMMA scintillator film.
[0089] Comparative Example 1
[0090] A Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystal, whose chemical formula is Cs3Cd2Cl7, and whose preparation method comprises the following steps:
[0091] Step 1: Place cadmium carbonate (0.2338 g) and cesium acetate (0.2719 g) in a 50 mL three-necked round-bottom flask, add octadecene (34 mL), oleic acid (5.6 mL), oleylamine (1.23 mL) and acetic acid (400 μL) in sequence, place on a constant temperature magnetic stirrer, evacuate the flask and heat to 60 ° C, and continue stirring for 30 minutes to obtain a precursor solution;
[0092] Step 2: Continue heating the precursor solution obtained in step 1 to 105° C. under vacuum and stir for two hours;
[0093] Step 3: Switch the atmosphere in the three-necked round-bottom flask to a nitrogen atmosphere, and raise the temperature to 240°C at a rate of 5°C / min. During this process, the solution gradually turns into a transparent yellow color. After reaching 240°C, quickly inject 800 μL of trimethylsilyl chloride with a syringe, and control the reaction time within 10 to 12 seconds.
[0094] Step 4: quickly place the three-necked round-bottom flask into an ice-water bath to cool and obtain a suspension;
[0095] Step 5: Divide the suspension obtained in step 4 into two equal parts and transfer them into 50 mL centrifuge tubes respectively. Add methyl acetate (the volume ratio of methyl acetate to the suspension is 1:1) as an anti-solvent and centrifuge at 10,000 rpm for 7 min to obtain a white precipitate.
[0096] Step 6: remove the supernatant, add 10 mL of n-hexane as a dispersant to the white precipitate obtained in step 5, use an ultrasonic cleaner to redisperse the powder to form a suspension, and then add 20 mL of methyl acetate to repeat the washing;
[0097] Step 7: The washed powder is composed of Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals and is dispersed in n-hexane for further characterization.
[0098] Performance Experiment
[0099] 1. X-ray powder diffraction phase analysis (XRD) structural characterization:
[0100] The divalent manganese ion doped cadmium-based metal halide nanocrystal scintillator materials in Examples 1 to 4 and the Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals in Example 1 were subjected to XRD analysis, wherein the X-ray powder diffraction phase analysis (XRD) was performed using a Bruker D8 Advance X-RAY powder diffractometer from Bruker, Germany. The specific test steps included: grinding the sample to be tested into powder, making the particles as fine and uniform as possible, and loading the ground sample into the sample slot so that the powder sample covered the entire sample slot as much as possible. The XRD spectrum of the sample was obtained by using Kα radiation (λ=1.54056Å) of a Cu target at room temperature and testing in the Bragg angle range of 10~80° with a step of 0.040°.
[0101] The test results are as follows Figure 2 As shown, Figure 2 A, 0% corresponds to the XRD spectrum of Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals without divalent manganese ions obtained in Example 1, and 5% corresponds to the XRD spectrum of Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals obtained in Example 1. 1.9 Mn 0.1 XRD spectrum of the cadmium-based metal halide nanocrystalline scintillator material doped with Cl7 divalent manganese ions, 10% corresponds to Cs3Cd obtained in Example 2 1.8 Mn 0.2 XRD spectrum of the cadmium-based metal halide nanocrystalline scintillator material doped with Cl7 divalent manganese ions, 15% corresponds to Cs3Cd obtained in Example 3 1.7 Mn 0.3 XRD spectrum of the cadmium-based metal halide nanocrystalline scintillator material doped with Cl7 divalent manganese ions, 20% corresponds to Cs3Cd obtained in Example 4 1.6 Mn 0.4 XRD spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions. Figure 2 B is the enlarged view of the 20-25° diffraction peak. Figure 2 It can be concluded that the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material Cs3Cd 2(1-a) Mn 2a Cl7 was compared with the standard PDF card (PDF#20-0952) of Cs3Cd2Cl7 provided in the crystallographic database ICDD. It was found that the peak positions and shapes were basically the same, and no new diffraction peaks appeared. The peak positions were due to the doping of Mn 2+ There is a slight shift, indicating that the above samples are all high-purity samples. The doped divalent manganese ions do not change Cs3Cd2Cl7, but Mn 2+ Successfully replaced Cd 2+The position of.
[0102] XRD results show that the divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material Cs3Cd 2(1-a) Mn 2a Cl7 is a triclinic system with a P1 space group structure, wherein the Cs3Cd 1.8 Mn 0.2 The unit cell constants of Cl7 scintillating material are a=10.6912Å, b=5.3456Å, c=27.5974Å, α=90°, β=90°, and γ=90°.
[0103] 2. Thermal stability test:
[0104] The Cs3Cd obtained in Example 2 1.8 Mn 0.2 The thermal stability performance test of the cadmium-based metal halide nanocrystalline scintillator material doped with Cl7 divalent manganese ions was carried out. The thermal stability performance test was carried out using the TGA 4000 thermogravimetric analyzer of the American PE company. The specific test steps include: placing the sample to be tested (13.625 mg) in an alumina cell and testing it in a nitrogen atmosphere (gas flow rate of 100 ml / min). The test temperature range is 23.5°C to 808°C. The test results are as follows: Figure 3 As shown, from Figure 3 It can be concluded that the Cs3Cd obtained in Example 2 1.8 Mn 0.2 The cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions still maintains structural integrity at 630°C, indicating that it has good thermal stability.
[0105] 3. Photoluminescence test experiment:
[0106] The photoluminescence performance of the divalent manganese ion-doped cadmium-based metal halide nanocrystal scintillator materials in Examples 1 to 4 and the Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals in Example 1 was tested, wherein the photoluminescence performance test was performed using the Edinburgh FS5 integrated steady-state transient fluorescence spectrometer of the Edinburgh Company of the United Kingdom, and the test conditions were as follows: the excitation light source was a Xe lamp, and ultraviolet light of a specific excitation band could be selected through the filtering system, the excitation slit was 1.5 mm, and the receiving slit was 1.5 mm.
[0107] The test results are as follows Figure 4 As shown in A, 0% corresponds to the photoluminescence excitation spectrum of the Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals not doped with divalent manganese ions obtained in Example 1, and 5% corresponds to the Cs3Cd2Cl7 obtained in Example 1. 1.9 Mn 0.1Photoluminescence excitation spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 10% corresponds to Cs3Cd obtained in Example 2 1.8 Mn 0.2 Photoluminescence excitation spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 15% corresponds to Cs3Cd obtained in Example 3 1.7 Mn 0.3 Photoluminescence excitation spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 20% corresponds to Cs3Cd obtained in Example 4 1.6 Mn 0.4 Photoluminescence excitation spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions; Figure 4 As shown in B, 0% corresponds to the photoluminescence emission spectrum of Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals without divalent manganese ions obtained in Example 1, and 5% corresponds to the photoluminescence emission spectrum of Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals obtained in Example 1. 1.9 Mn 0.1 Photoluminescence emission spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 10% corresponds to Cs3Cd obtained in Example 2 1.8 Mn 0.2 Photoluminescence emission spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 15% corresponds to Cs3Cd obtained in Example 3 1.7 Mn 0.3 Photoluminescence emission spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions, 20% corresponds to Cs3Cd obtained in Example 4 1.6 Mn 0.4 Photoluminescence emission spectrum of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions. Figure 4 It can be concluded that the Cs3Cd2Cl7 all-inorganic cadmium-based metal halide nanocrystals obtained in Comparative Example 1 exhibit 515nm blue light emission, and the Cs3Cd2Cl7 obtained in Examples 1 to 4 2(1-a) Mn 2a The cadmium-based metal halide nanocrystal scintillator materials doped with Cl7 divalent manganese ions showed the strongest excitation at 255nm under the monitoring of 573nm, and showed yellow light emission at 573nm under the optimal wavelength excitation of 255nm ultraviolet light. And as the doping concentration increases, the intensity of yellow light emission becomes higher and higher. When the doping concentration is 10%, that is, Cs3Cd obtained in Example 2 1.8 Mn 0.2The photoluminescence performance of cadmium-based metal halide nanocrystal scintillator materials doped with Cl7 divalent manganese ions is the best.
[0108] 4. Fluorescence lifetime test experiment:
[0109] The Cs3Cd obtained in Example 2 1.8 Mn 0.2 The fluorescence lifetime test was carried out on the cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions. The excitation light source for the fluorescence lifetime test was a μF2 microsecond pulse xenon lamp. The fitting model used in calculating the fluorescence lifetime was ExpDec2, and the determination coefficient (COD) of the fitting was 0.9988.
[0110] The experimental spectrum of fluorescence lifetime test is as follows Figure 5 As shown, from Figure 5 It can be concluded that under the optimal wavelength excitation of ultraviolet light 255nm, Cs3Cd 1.8 Mn 0.2 The fluorescence lifetime of the cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions is 0.652μs.
[0111] 5. Quantum efficiency test experiment:
[0112] The Cs3Cd obtained in Example 2 1.8 Mn 0.2 The quantum efficiency of the cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions was tested. The quantum efficiency test was obtained using the Edinburgh Steady-State / Transient Fluorescence Spectrometer FLS-1000 fluorescence spectrometer equipped with a Xe lamp from Edinburgh, UK. The test used an excitation light source of 255 nm, and the quantum efficiency was calculated as follows: , where I S is the luminescence emission spectrum of the sample, E R is the excitation light spectrum from an empty integrating sphere (without sample), E S is the excitation spectrum of the sample.
[0113] The quantum efficiency test results are as follows: Figure 6 As shown, from Figure 6 It can be concluded that the Cs3Cd obtained in Example 2 1.8 Mn 0.2 Fluorescence efficiency of cadmium-based metal halide nanocrystal scintillator material doped with Cl7 divalent manganese ions: the quantum efficiency is 20.6%.
[0114] 6. Transmission electron microscope (TEM) test experiment:
[0115] The Cs3Cd obtained in Example 2 1.8 Mn 0.2The TEM image test of the cadmium-based metal halide nanocrystalline scintillator material doped with Cl7 divalent manganese ions was carried out. The TEM was taken using a Tecnai G2F20 transmission electron microscope produced by FEI Company.
[0116] TEM image results are as follows Figure 7 As shown, from Figure 7 It can be seen that the Cs3Cd 1.8 Mn 0.2 The Cl7 divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material has a grain size of 200 nm, uniform particles, good dispersion, and good crystallinity.
[0117] 7. X-ray scintillation performance test experiment:
[0118] The Cs3Cd obtained in Example 5 1.8 Mn 0.2 The X-ray scintillation performance of Cl7@PS scintillator film and commercial scintillator (CsI: Tl) was tested. The X-ray scintillation performance was measured by the HVC1800 photodetector spectral response measurement system of Beijing Zhuoli Hanguang Instrument Co., Ltd. The X-ray source used was the Monoblock source of Moxtek (USA). The tube voltage of the X-ray tube was 70 kV, the tube current of the X-ray tube was 170 mA, and the distance between the sample and the X-ray tube was 5 cm.
[0119] The experimental spectrum of the measured X-ray scintillation performance is shown in Figure 8 As shown, the Cs3Cd obtained in Example 5 1.8 Mn 0.2 The Cl7@PS scintillator film exhibits yellow luminescence at 573 nm. Figure 8 It can be seen that under the same test conditions, the Cs3Cd 1.8 Mn 0.2 The scintillation intensity of the Cl7@PS scintillator film is about 1.3067 times that of the CsI: Tl wafer, and the light yield is 52,269 photons MeV -1 (The specific value is based on the comparison of the integrated area. CsI: Tl is a commercial standard comparison sample. The default light yield is 40,000 photons MeV -1 , Cs3Cd obtained in Example 5 1.8 Mn 0.2 The light yield of the Cl7@PS scintillator film is 40,000×1.3067=52,269 photons MeV -1). Therefore, the performance of the scintillator film obtained by the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material prepared by the present invention has exceeded that of commercial scintillator materials, and the preparation cost of the present invention is low and has great advantages in industrial production.
[0120] Example 5 Cs3Cd obtained 1.8 Mn 0.2 The experimental test results of the minimum detection limit of X-rays of Cl7@PS scintillator film are as follows: Fig. 9 As shown, the change of the X-ray dose can be achieved by fixing the tube voltage of the X-ray tube and changing the tube current of the X-ray tube. The actual detected dose is calibrated by the RAMION radiation dosimeter. The detection limit is also an important parameter of the X-ray detector, which determines the minimum detection dose of the X-ray detector. The International Union of Applied Chemistry (IU-PAC) defines the detection limit as the equivalent dose rate that produces a signal greater than 3 times the noise level (signal-to-noise ratio [SNR] = 3). Therefore, the Cs3Cd obtained in Example 5 can be obtained. 1.8 Mn 0.2 The minimum detection limit of Cl7@PS scintillator film is 4.0138 μGy air / s, lower than the conventional medical diagnostic dose standard of 5.50μGy air / s. This shows that the sample has sensitive X-ray detection capability.
[0121] 8. X-ray imaging test experiment:
[0122] The Cs3Cd obtained in Example 5 1.8 Mn 0.2 The Cl7@PS scintillator film was subjected to X-ray imaging test. Specifically, the Cs3Cd 1.8 Mn 0.2 The Cl7@PS scintillator film was placed in close contact with the imaging object, the X-ray source was placed at the far end of the object side, and the image of the scintillator side was captured with a digital camera.
[0123] The test results are as follows Fig.10 , 11 As shown in 12, it can be seen from the test results that the Cs3Cd 1.8 Mn 0.2 The Cl7@PS scintillator film can transform the invisible spring inside the capsule ( Fig.10 )、Metal Pattern( Fig.11 ) and standard lead sheet ( Fig.12 A and B) Clear imaging of three types of objects, by Fig.12 As can be seen from A and B, Cs3Cd 1.8 Mn 0.2The imaging resolution of Cl7@PS scintillator film reaches 16 line pairs per millimeter (lp / mm).
[0124] The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material of the present invention has small particles and good dispersibility, exhibits yellow light emission at 573nm, and has a quantum efficiency of 20.6%. The light excitation is generated from the tetracoordinated Mn 2+ of 4 T1− 6 A1 energy level transition, with high radiation efficiency, large Stokes shift, and low self-absorption, overcomes the inevitable self-absorption problem of lead-based halide perovskites. In addition, the material also has excellent X-ray scintillation performance, with a scintillation intensity of about 1.3067 times that of CsI:Tl and a light yield of 52,269 photons MeV -1 , and overcomes the problems of poor radiation stability and toxicity of lead-based halide perovskites, and has important commercial application value in the field of scintillating materials. The preparation method is simple, the preparation cost is low, it is green and pollution-free, the purity of the obtained material is high, and it is suitable for large-scale industrial production. The scintillator film prepared by the present invention by selecting a suitable method for preparing the scintillator film solves the technical problems of defects such as uneven scintillator film and low radiation luminescence intensity in the existing scintillator film forming technology. The present invention improves the resolution of the scintillator film by improving the uniformity of the texture of the scintillator film, reducing the thickness of the scintillator film, and increasing the transparency of the scintillator film. The scintillator film of the present invention has high-performance X-ray detection capabilities, which can further improve the spatial resolution of imaging display devices, which is crucial for high-quality imaging, and has important commercial application value in the field of high-energy particle detection and imaging display materials.
[0125] The present invention adopts a hot injection method to prepare a divalent manganese ion doped cadmium-based metal halide nanocrystalline scintillator material, the chemical formula of which is Cs3Cd2Cl7, and the crystal structure belongs to the tetragonal system, the I4 / mmm space group, and has a special characteristic Ruddlesden-Popper (RP) structure, Cd atoms and Cl atoms form a 6-coordinated CdCl6 octahedral structure, in which the cation Cs is evenly distributed in the octahedral gap. The RP structure is composed of CdCl6 octahedral sheets with shared corners in a square geometry stacked in an ABAB order along the c-axis, which provides a higher possibility for doping with other ions, thereby achieving more excellent luminescence performance.
[0126] The Cl source used in the present invention is trimethylchlorosilane, which provides supersaturated Cl ions for the hot injection method used in the present invention. During the reaction, the precursor solution is quickly injected into the hot reaction solution using a syringe, so that the supersaturation of the solution increases instantly, uniform nucleation occurs, and the growth state of the grains remains basically consistent, ensuring the monodispersity of the product. When trimethylchlorosilane participates in the reaction, the newly generated silicon-containing groups or intermediates are also immediately "captured" and wrapped by oleic acid and oleylamine. The microenvironment constructed by the surfactant makes it difficult for these active intermediates to diffuse and aggregate at will, but reacts with adjacent suitable species in a controlled manner, ensuring the fine regulation of the growth process, and there will be no situation where an overly large nucleus is generated due to excessive aggregation. Therefore, the nanocrystalline material prepared by the present invention has the characteristics of uniform particles and good dispersibility.
[0127] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.
Claims
1. A divalent manganese ion-doped cadmium-based metal halide nanocrystal scintillator material, characterized in that: The general chemical formula is: A3B 2(1-a) Mn 2a X7, wherein A is Cs, B is Cd, X is Cl, and 0<a≤20.
2. The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material according to claim 1, characterized in that: 0<a≤0.2。 3. The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material according to claim 2, characterized in that: a is 0.
1.
4. A method for preparing the divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: Weigh each raw material according to the general chemical formula to prepare a precursor solution; Step 2, heating the precursor solution under vacuum; Step 3: The vacuum environment is switched to an inert gas atmosphere, and a hot injection process is used to prepare a divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material.
5. The method according to claim 4, characterized in that Step three specifically includes: switching the vacuum environment to a nitrogen atmosphere, raising the temperature to 240°C at a rate of 5°C / min, rapidly injecting 800 μL of trimethylchlorosilane with a syringe, and controlling the reaction time within 10 to 12 seconds.
6. The method according to claim 4, characterized in that Step one specifically includes: weighing cadmium carbonate, cesium acetate and manganese carbonate according to the general chemical formula, placing them in a 50 mL three-necked round-bottom flask, adding octadecene, oleic acid, oleylamine and acetic acid in sequence, placing the flask on a constant temperature magnetic stirrer, evacuating the flask and heating it to 60°C, and stirring it continuously for 30 minutes to obtain a precursor solution.
7. A scintillator film, characterized in that: The invention comprises the cadmium-based metal halide nanocrystalline scintillator material doped with divalent manganese ions as claimed in any one of claims 1 to 3.
8. A method for preparing the scintillator thin film according to claim 7, characterized in that: include: The divalent manganese ion-doped cadmium-based metal halide nanocrystalline scintillator material as claimed in any one of claims 1 to 3 is dispersed in a polymer precursor, and a scintillator film is prepared by a blade coating method.
9. The method according to claim 8, characterized in that The polymer is polystyrene, polyvinylidene fluoride or polymethyl methacrylate.
10. Application of the scintillator film according to claim 7 in X-ray medical imaging, non-destructive testing, and industrial flaw detection.
Citation Information
Patent Citations
Humidity-sensitive irreversible fluorescent anti-counterfeiting material as well as preparation method and application thereof
CN114891499A
Divalent metal cation doped Cs3Cu2I5 nanocrystal as well as preparation method and application thereof
CN114940510A
Mn-doped Cs2CdCl4 scintillator
CN115975633A
Manganese-doped enhanced ionizing radiation luminescence halide scintillator and preparation method and application thereof
CN117431067A
Zero-dimensional organic zinc-based halide scintillator material and preparation method and application thereof
CN119020020A
Cited By
Metal cation doped zero-dimensional organic-inorganic hybrid zinc-based halide scintillator materials, methods of making and applications thereof
CN119955510B